Gaya Belajar Anak Homeschooling (Studi pada Keluarga Pelaku Homeschooling) - Khair, Alfin Miftahul; Fadillah, Galih Fajar (Universitas Negeri Padang, 2017)
Homeschooling could be an education alternatives, the substance of activities of the school. The child is learns everything under control and supervise of parent. Families must have a strong commitment within the practice. This study is a qualitative phenomenological approach focused discusses a phenomenon about homeschooling. The aim of this research is to know the methods of study used in the process of teaching and learning results gained from the learning process through homeschooling. Collecting data is using the method of observation, interview and documentation. Data analysis using qualitative descriptive method and the validity of data is done by triangulation. The results are: 1) in behavioristic kids are love learning because fun and can be anywhere. Cognitively, kids can customize his ability to learn. In humanistic kids are aware to the conditions and environments around them. 2) Learning Outcome demonstrate the kids progress in cognitive, affective and psychomotor. Â